Financial Sector Liberalization and Financial Instability: Case of Selected Southern African Development Community Member Countries - Nolungelo Cele; Kapingura FM (Journal of Economics and Behavioral Studies, 2018)
The importance of financial liberalization is well documented in the literature. However, there has been an emergency of studies, which indicate that this can be another channel through which financial instability is generated in the domestic economy. Utilising data from four SADC countries, the empirical findings show that financial reforms are positively related to financial instability in almost all the specifications. The empirical results further revealed that financial instability intensifies in the face of a financial crisis. The result suggests that financial liberalization can therefore be another source of financial instability in the region. The empirical results imply that though policymakers should liberalise the financial system, policies aimed at maintaining financial stability should also be promoted.